Blood lead level and cognitive performance in Ukrainian schoolchildren - Hnidoi, Ihor (Psychosomatic Medicine and General Practice, 2023)
Background. Modern systematic review and meta-analysis of case-control studies demonstrate the large effect of lead exposure on IQ test scores in children under 12 years. The World Health Organization estimate that lead exposure causes 30% of the global burden of idiopathic intellectual disability. In this regard, in the most developed countries, for example, the United States, there are special government programs, International Lead Poisoning Prevention Weeks, which present an opportunity to initiate long-overdue reforms. In Ukraine, there are no state programs of such a scale as in the United States. Research on the study and limitation of the ecopathological effect of lead on the psychosomatic state of Ukrainian schoolchildren is still rare. The aim of this study was to evaluate the effect of blood lead levels on cognitive sphere indexes in urban schoolchildren resident in Odesa, Ukraine. Materials and Methods. 92 children of random sample were examined, aged 7 to 15 years. Determination of lead was carried out in heparinized venous blood by the method of atomic absorption spectrometry with electrothermal atomization. According to blood lead level, the children were divided into 4 groups: 1) up to 49 μg/l, n = 57; 2) from 50 to 99 μg/l, n = 16; 3) from 100 to149 μg/l, n = 14; 4) more than 150 μg/l, n = 5. The groups were homogeneous in terms of such indicators as age, sex of children, diseases they suffered, education and social position of parents, family wealth, peculiarities of pregnancy and childbirth by a given child in the mother. Indicators of the cognitive sphere were determined according to the methods recommended for research in children aged 7 to 15 years. The control was the first group of children. Results. The deviation rate from the optimal level of figure recognition in children of the second group (1.38±0.27) and the third group (1.43±0.27) was significantly higher than in children of the first group (0.73±0.12 points). The number of correctly reproduced images by children of the third group (7.86± 0.51) and the fourth group (7.00±0.89) was significantly less than that of children of the first group (9.12±0.41). Both indicators reflect the state of short-term memory. The number of words memorized by Luria’s method, reproduced after 1 hour, was significantly less in schoolchildren of the second group (7.87±0.37), the third group (6.50±0.57), the fourth group (6.20±1.07) than in schoolchildren of the first group (8.77±0.14). This indicator reflects the state of long-term memory. The concentration of attention on the Bourdon test in children of the third group (85.6±18.4 c.u.) was significantly lower than in children of the first group (126.9±12.8 c.u.). Children of the same group worked longer with the Gorbov table (283.0±22.6 s) compared to children of the first group (221.1±9.2 s). Schoolchildren of the second and third groups showed worse results of attention tests compared to the first group, such as the indicator of switching attention on the Bourdon test (respectively 67.64±4.06% and 71.84±3.17% vs. 83.34±2.14%), the number of errors when working with the Gorbov table (respectively 2.87±0.54 and 3.00±0.64 against 1.16±0.14), the time of switching attention (respectively 131.8±12.3 s and 146.9±17.5 s versus 101.7±6.3 s). In addition, the number of uncorrected errors in the Halperin, Kabylitskaya test was higher in children of the third group (4.92±0.64) and the fourth group (4.80±0.80) than in children of the first group (2.87±0.26). Conclusion. Increasing the level of lead in the blood of Ukrainian schoolchildren negatively affects their cognitive sphere, impairing short-term and long-term memory, reducing concentration, and slowing down the rate of switching attention.